2016
DOI: 10.1021/acs.est.6b00965
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxyethylene Tallow Amine, a Glyphosate Formulation Adjuvant: Soil Adsorption Characteristics, Degradation Profile, and Occurrence on Selected Soils from Agricultural Fields in Iowa, Illinois, Indiana, Kansas, Mississippi, and Missouri

Abstract: Polyoxyethylene tallow amine (POEA) is an inert ingredient added to formulations of glyphosate, the most widely applied agricultural herbicide. POEA has been shown to have toxic effects to some aquatic organisms making the potential transport of POEA from the application site into the environment an important concern. This study characterized the adsorption of POEA to soils and assessed its occurrence and homologue distribution in agricultural soils from six states. Adsorption experiments of POEA to selected s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Furthermore, the finding that POEA is widely found in fields in the United States where glyphosate-based herbicides are applied ( 37 ) raises concerns that this and other classes of pesticide adjuvants may be entering the food and feed chain undetected, with as yet unknown health consequences.…”
Section: Adjuvants Can Be More Toxic Than Active Principlesmentioning
confidence: 99%
“…Furthermore, the finding that POEA is widely found in fields in the United States where glyphosate-based herbicides are applied ( 37 ) raises concerns that this and other classes of pesticide adjuvants may be entering the food and feed chain undetected, with as yet unknown health consequences.…”
Section: Adjuvants Can Be More Toxic Than Active Principlesmentioning
confidence: 99%
“…The latter are, in general, not identified on product labels and can be claimed confidential business information. The Roundup product line (Monsanto) is the major and best known formulation that, as a surfactant, very often contains polyethoxylated tallow amine (POEA), a complex mixture of di-ethoxylates of unsaturated and saturated tallow amines characterized by their oxide/tallow amine ratio (typically 15% or less of the final formulation) (Tush and Meyer 2016 ). POEA are significantly more toxic to animals, e.g., amphibia, than glyphosate itself (Howe et al 2004 ) and have been shown to be active principles of human cell toxicity (Mesnage et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on Langmuir isotherm principles, adsorption occurs in monolayers on the surface, which contains a finite number of identical adsorption sites [44]. It also assumes that the adsorption energies at the surface of the adsorbent are uniform, that there is no adsorbent transmigration in the surface plane and that there is no interaction among adsorbed molecules [12].…”
Section: Adsorption Isothermsmentioning
confidence: 99%